The impact of arbuscular mycorrhizal colonization on flooding response of Medicago truncatula - Safavi-Rizi, Vajiheh; Friedlein, Helen; Safavi-Rizi, Sayedhamid; Krajinski-Barth, Franziska (Frontiers in Plant Science, 2025)
Climate change is expected to lead to an increase in precipitation and flooding. Consequently, plants that are adapted to dry conditions have to adjust to frequent flooding periods. In this study, we investigate the flooding response of Medicago truncatula, a Mediterranean plant adapted to warm and dry conditions. Arbuscular mycorrhizal (AM) symbiosis plays a key role in enhancing plant growth and stress tolerance, yet its interactions with environmental stressors such as flooding remain poorly understood. In this study, we investigated the effects of mycorrhizal colonization and flooding stress on the growth, physiological and molecular responses of M. truncatula wild-type (WT) and ha1-2 mutant lines. ha1-2 mutant plants are unable to form a functional symbiosis with AM fungi as they are impaired in the proton pump required for phosphate transport from AM fungus to the plant. Over a six-week period, WT and ha1-2 plants were cultivated in the presence of Rhizophagus irregularis and subsequently subjected to a 10-day waterlogging treatment. Our results indicated that under control and also flooding conditions, WT mycorrhizal plants exhibited increased dry biomass compared to non-mycorrhizal WT plants. In contrast, the ha1-2 mutant plants did not show the enhanced biomass gain associated with AM symbiosis. The decline in biomass in response to flooding was more pronounced in mycorrhizal plants compared to the non-mycorrhizal plants. In mycorrhizal plants, flooding suppressed the transcript levels of MtPt4 gene in both WT, although not significantly, and ha1-2 mutant lines. Gene expression analysis showed modulation in genes related to nitrogen metabolism and hypoxic response. A strong upregulation of the MtGNS1 transcript ( 3000-fold) was observed in WT, however, this upregulation was milder in the ha1-2 plants. Our findings suggest that while AMF symbiosis positively affects plant biomass under control conditions, its beneficial effects were attenuated under flooding stress. Future research will focus on understanding the molecular mechanisms behind AMF modulation of flooding stress responses, including nutrient uptake and metabolism, stress tolerance, and recovery post-flooding. These results will facilitate the enhancement of AMF-based strategies to improve plant resilience against climate change-induced flooding events.